Pengaruh Diameter Kawat dan Panjang Koil Pegas Tekan terhadap Defleksi pada Sistem Getaran Ayak - Yokasing, Yohanes Benediktus; Santhiarsa, I.Gusti Ngurah Nitya; Parwata, I. Made; Lokantara, I. Putu (Universitas Muhammadiyah Metro, 2025)
The design of a vibration-based screening system requires adjustment of the compression spring characteristics to meet the required amplitude and working frequency. This study analyzes the effect of wire diameter (d) and spring coil length (No) on spring deflection (Î´) and stiffness (k) as key parameters in the design of vibratory sieve systems. A quantitative approach was employed through deflection testing using a spring tester and performance graphs. The results show that increasing the wire diameter from 3 mm to 4 mm reduces deflection by up to 38% and increases spring stiffness by approximately 50%. Conversely, increasing the coil length from 80 mm to 120 mm raises deflection by about Â±48%. The spring stiffness constant ranges from 2.4 N/mm to 3.8 N/mm, depending on the dimensional combination. The combination of d = 4 mm and No = 80 mm is suitable for low-frequency vibrations, while d = 3 mm and No = 120 mm is appropriate for high-frequency vibrations. These findings provide technical guidance for adjusting spring characteristics to match the vibration design targets of screening systems, particularly in the processing of both light and heavy materials.